Path planning for an unmanned terrestrial vehicle in an obstacle ridden environment - Ferreira, Thomas Ignatius (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2009.